Investigation on the phenytoin sodium channel-blocker effect in PDT of MDA MB 231 breast cancer using a positively charged PS - HomaSadat Esfahani; Reza Hosseinzadeh; Khatereh Khorsandi (Scientific Reports)
Abstract Cancer therapy, due to the rising number of detected and reported cases, is one of the most important goals of scientists worldwide. Among these, there is a strong interest in using effective noninvasive protocols for cancer therapy. This study aims to investigate the combined effect of phenytoin, a sodium channel-blocker, with Methylene Blue, a photosensitizer used in photodynamic therapy (PDT), on breast cancer cell viability and uptake. To determine the appropriate concentrations of phenytoin in Methylene Blue solutions, we measured the intensity of the samples at excitation wavelengths between 200 and 800 nm using a spectrophotometer. Breast cancer cell viability was evaluated in four research groups using the MTT assay under both light and dark conditions. Morphological characterization was performed using an inverted light microscope and dual acridine orange/ethidium bromide (AO/EB) fluorescent staining. The hypothesis focuses on the effect of pre-treatment with phenytoin on cellular uptake of Methylene Blue and the impact on cell viability. These effects were examined across four distinct treatment groups to comprehensively assess the potential benefits of combined treatment. The results showed that the combination treatment not only increased cellular uptake but also demonstrated higher toxicity to cancer cells, suggesting enhanced therapeutic potential. Additionally, the study highlights the importance of noninvasive protocols in cancer therapy, paving the way for further research into optimizing such treatments.